2013
DOI: 10.1259/bjr.20120174
|View full text |Cite
|
Sign up to set email alerts
|

Whole-tumour CT-perfusion of unresectable lung cancer for the monitoring of anti-angiogenetic chemotherapy effects

Abstract: Objective: To determine whether CT-perfusion (CT-p) can be used to evaluate the effects of chemotherapy and anti-angiogenic treatment in patients with non-small-cell lung carcinoma (NSCLC) and whether CT-p and standard therapeutic response assessment (RECIST) data obtained before and after therapy correlate. Methods: 55 patients with unresectable NSCLC underwent CT-p before the beginning of therapy and 50 of them repeated CT-p 90 days after it. Therapeutic protocol included platinum-based doublets plus bevaciz… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
27
1

Year Published

2014
2014
2020
2020

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 26 publications
(30 citation statements)
references
References 20 publications
2
27
1
Order By: Relevance
“…After chemo-radiation therapy, findings at perfusion CT can act as a significant predictor of early tumor response and OS among NSCLC patients. CT-perfusion can adequately evaluate therapy-induced alterations in NSCLC, and perfusion parameters correlate with therapy response assessment performed with RECIST criteria (40). Evaluating perfusion parameters, CT-perfusion can demonstrate therapy-induced changes in patients with different types of lung cancer and identify response to treatment with excellent agreement to RECIST measurements.…”
Section: Dynamic Contrast-enhanced Ct (Dce-ct): Volume Perfusion Ctmentioning
confidence: 99%
“…After chemo-radiation therapy, findings at perfusion CT can act as a significant predictor of early tumor response and OS among NSCLC patients. CT-perfusion can adequately evaluate therapy-induced alterations in NSCLC, and perfusion parameters correlate with therapy response assessment performed with RECIST criteria (40). Evaluating perfusion parameters, CT-perfusion can demonstrate therapy-induced changes in patients with different types of lung cancer and identify response to treatment with excellent agreement to RECIST measurements.…”
Section: Dynamic Contrast-enhanced Ct (Dce-ct): Volume Perfusion Ctmentioning
confidence: 99%
“…Investigative Radiology • Volume 00, Number 00, Month 2015 coworkers 36 recently showed that the comparably high BF of LCC shows the best response of all NSCLC subtypes to antiangiogenic treatment. We found significant differences in pulmonary PI max using a tumor volume cutoff of 3.5 cm 3 , with higher pulmonary PI max in larger tumors.…”
Section: Nguyen-kim Et Almentioning
confidence: 99%
“…9,15,46-48 Tacelli et al 19,36 showed a significant reduction in total tumor vascular volume during treatment with chemotherapy using anti-vascular endothelial growth factor drugs. Fraioli et al 19,36 demonstrated a significant difference in BF and BV in LCC patients for partial response and progressive disease.…”
Section: Nguyen-kim Et Almentioning
confidence: 99%
See 1 more Smart Citation
“…Two other studies [24,87] investigated the role of VPCT in therapy response monitoring in lung cancer. They compared NSCLC before and during anti-angiogenetic treatment.…”
Section: Lungmentioning
confidence: 99%